Reconciling Output and Unemployment Fiscal Multipliers - Kim, Tae Bong (Global Economic Review, 2019)
This paper provides a macroeconomic model that can simultaneously explain output and unemployment multipliers which are consistent with empirical evidence. To this end, this paper has merged and investigated a model with deep habit formation in private and public consumptions and a model with a labour market friction that generates involuntary unemployment stemming from the monopolistic power of differentiated labour services. The model with a baseline calibration seems to produce quantitatively plausible responses of key macroeconomic variables in response to a government expenditure shock.
Keywords: deep habit; Fiscal multiplier; unemployment